Class, chaos, and the construction of community. [article]. - Piff, Paul K.
Chaotic conditions are prevalent and threatening feature of social life. five studies examined whether social class underlies divergent responses to perceptions of chaos in one's social environments and outcomes. The authors hypothesized that when coping with perceptions of chaos, lower class individuals tend to prioritize community, relative to upper class individuals, who instead tend to prioritize materials wealth. Consistent with these pre3dictions, when personally confronting chaos, lower class individuals were commonly oriented (Study 1), more connected with their community (|Study 2), and more likely to volunteer for a community-building project (Study 3), compared to upper class individuals to express greater reliance on wealth (Study 4) and prefer financial gain over membership in a close-knit community (Study 5), relative to lower class and cope with its threatening consequences. - (from the authors)
Keywords: Stancato, Daniel M; Social class; Chaos; Coping; Communal relationships; Material wealth